On the connections between relations, relation schemes and keys - Thi, Vũ Đức (Journal of Computer Science and Cybernetics, 2016)
The relation, relation schemes, keys and antikeys are essential concepts in the relational datamodel. In this paper, we present some computational connections between relations, relation schemes and sets of minimal keys. Some another combinatorial results connecting them also are given.